2018
DOI: 10.1002/rcm.8065
|View full text |Cite
|
Sign up to set email alerts
|

Food provisioning in Magellanic penguins as inferred from stable isotope ratios

Abstract: We have developed an approach that provides the first assessment of the extent of differential food provisioning between male and female Magellanic penguins. Results suggest chicks have a diet more similar to that of their male parent, probably related to the higher trophic level of male penguin prey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 58 publications
2
8
0
Order By: Relevance
“…Because this difference is driven by the δ 13 C, it is most likely that both sexes prey on similar trophic level prey in different areas in the sea. Additionally, stable isotope signatures were similar to penguin breeding in northern colonies during chick rearing (Ciancio et al ), which agrees with the main northward migration shown by GLS tags. As expected, sexes showed similar isotopic niches later in the season during chick rearing while they behave as central place foragers and showed similar stable isotope values compared to other predators in the region (Ciancio et al ).…”
Section: Discussionsupporting
confidence: 83%
“…Because this difference is driven by the δ 13 C, it is most likely that both sexes prey on similar trophic level prey in different areas in the sea. Additionally, stable isotope signatures were similar to penguin breeding in northern colonies during chick rearing (Ciancio et al ), which agrees with the main northward migration shown by GLS tags. As expected, sexes showed similar isotopic niches later in the season during chick rearing while they behave as central place foragers and showed similar stable isotope values compared to other predators in the region (Ciancio et al ).…”
Section: Discussionsupporting
confidence: 83%
“…, Ciancio et al. ). Evidence from non‐breeding areas suggests that female Magellanic Penguins are more susceptible to starvation.…”
Section: Discussionmentioning
confidence: 97%
“…For example, recent studies suggest that males provision more food to Magellanic Penguin chicks than do females (Ciancio et al. ), despite similar duration foraging trips during the breeding season.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations